2012
DOI: 10.1051/0004-6361/201118180
|View full text |Cite
|
Sign up to set email alerts
|

Subarcsecond SMA observations of the prototype Class 0 object VLA1623 at 1.3 mm: a single protostar with a structured outflow cavity?

Abstract: We present 1.3-mm subarcsecond SMA observations of the prototypical Class 0 protostar VLA1623. We report the detection of 1.3-mm continuum emission both from the central protostellar component VLA1623 and two additional sources, Knot-A and Knot-B, which have been already detected at longer wavelengths. Knot-A and Knot-B are both located along the western cavity wall opened by the protostellar outflow from VLA1623. Our SMA observations moreover show that these two continuum sources are associated with bright, h… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 31 publications
1
22
1
Order By: Relevance
“…In a similar vein, there have been hypotheses put forward that some clearly detected continuum sources were features produced by outflow interactions (Maury et al 2010(Maury et al , 2012. However, further study over the past several years has found that, the continuum features that were suggested to be outflow knots in VLA 1623, are definitively real protostars Sadavoy et al 2018;Harris et al 2018).…”
Section: Non-detections Of Companionsmentioning
confidence: 92%
“…In a similar vein, there have been hypotheses put forward that some clearly detected continuum sources were features produced by outflow interactions (Maury et al 2010(Maury et al , 2012. However, further study over the past several years has found that, the continuum features that were suggested to be outflow knots in VLA 1623, are definitively real protostars Sadavoy et al 2018;Harris et al 2018).…”
Section: Non-detections Of Companionsmentioning
confidence: 92%
“…2 along with a more spatially and kinematically separated Class I component, VLA 1623W, at a distance ∼ 10. 5 and kinematic offset 3 − 4 km/s from the VLA 1623AB subsystem (Bontemps & Andre 1997;Looney et al 2000;Maury et al 2012;Murillo et al 2013). The Keplerian disk in this system orbits the easternmost A component and suggests a component mass of 0.1-0.2 M (Murillo et al 2013).…”
Section: Introductionmentioning
confidence: 99%
“…This has, however, been challenged by the interferometric observations presented in Ward- Thompson et al (2011). An alternative interpretation is that the observed continuum sources close to VLA 1623 are knots in the north-western jet (Maury et al 2012).…”
Section: Introductionmentioning
confidence: 99%